Management of tooth surface loss in a teenager patient with medical problems - a case report - Harun, Nor Asilah (2012)
Tooth wear is recognized as a major problem in children and adults. Prevalence data indicated that dental erosion of young people increases over time. The UK Child Dental Health Survey (CDHS), 2003 reported that 25% of 15 year olds had erosion at the palatal surfaces of their incisors. Erosion can cause irreversible damage to the permanent teeth and may compromise the dentition for the entire lifetime if untreated. Therefore, knowledge of the etiological factors, early diagnosis, appropriate prevention and management are crucial.